2019
DOI: 10.1111/sltb.12570
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation, Suicidal Attempts, and Self‐Harm in the UK Armed Forces

Abstract: Introduction In the UK military, suicide is infrequent and studies of self‐harm behavior in this population are rare. Objectives To compare lifetime self‐harm rates estimated on three occasions between 2004 and 2016 and to explore the associates of lifetime self‐harm. Method Three phases of a UK AF cohort study (n = 10,272, 9,990, and 8,581, respectively) provided data. Telephone interviews assessed associates of self‐harm among cohort members who reported subjective mental health problems in the past 3 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(53 citation statements)
references
References 50 publications
(59 reference statements)
0
52
1
Order By: Relevance
“…In the UK, Rhead et al ( 2020 ) found that veterans of recent military operations were more likely to report common mental disorders (23% v. 16%), PTSD (8% v. 5%) and alcohol misuse (11% v. 6%) at a higher prevalence than non-veterans. Jones, Sharp, Phillips, & Stevelink ( 2019 ) found an upward trend in self-harming among active personnel and veterans from 1.9% in 2004–2006, to 3.8% in 2007–2009, to 6.6% in 2014–2016. In the same study, 9.7% of respondents had attempted suicide in their lifetime, whereas nearly 48% had experienced suicide ideation (Jones et al, 2019 ).…”
Section: Combat and Mental Health: Understanding Moral Injurymentioning
confidence: 99%
“…In the UK, Rhead et al ( 2020 ) found that veterans of recent military operations were more likely to report common mental disorders (23% v. 16%), PTSD (8% v. 5%) and alcohol misuse (11% v. 6%) at a higher prevalence than non-veterans. Jones, Sharp, Phillips, & Stevelink ( 2019 ) found an upward trend in self-harming among active personnel and veterans from 1.9% in 2004–2006, to 3.8% in 2007–2009, to 6.6% in 2014–2016. In the same study, 9.7% of respondents had attempted suicide in their lifetime, whereas nearly 48% had experienced suicide ideation (Jones et al, 2019 ).…”
Section: Combat and Mental Health: Understanding Moral Injurymentioning
confidence: 99%
“…Higher rates were found among army veterans [39]. Some reports show women to be at higher risk for self-harm compared to men [40], but no explanation is provided for this phenomenon.…”
Section: Uk Armed Forcesmentioning
confidence: 91%
“…Suicide attempts were not included in this report [41]. A 2019 study addressed the issue using data from the King's Centre for Military Health Research and from a telephone survey [40]. The findings from the telephone survey showed that 9.7% of UKAF members had attempted suicide at least once during their lifetime.…”
Section: Uk Armed Forcesmentioning
confidence: 99%
“…This is particularly evident among younger males of lower ranks (Simkus et al, 2017; US Department of Veterans Affairs, 2019). Although there is less research available on suicidal ideation, plans and attempts, the available findings likewise indicate increased rates in veterans compared to both current serving and community samples in the United States (Nock et al, 2008), the United Kingdom (Jones et al, 2019) and Canada (Simkus et al, 2017).…”
Section: Prevalence Of Completed Suicides and Suicidality In Military Populationsmentioning
confidence: 99%